Exploration of PDCoV-induced apoptosis through mitochondrial dynamics imbalance and the antagonistic effect of SeNPs - Ren, Zhihua; Yu, Yueru; Zhang, Xiaojie; Wang, Qiuxiang; Deng, Junliang; Chen, Chaoxi; Shi, Riyi; Wei, Zhanyong; Hu, Hui (Frontiers in Immunology, 2022)
Porcine Deltacoronavirus (PDCoV), an enveloped positive-strand RNA virus that causes respiratory and gastrointestinal diseases, is widely spread worldwide, but there is no effective drug or vaccine against it. This experiment investigated the effect of PDCoV on ST cell apoptosis, mitochondrial dynamics, and the antagonistic effect of Selenium Nano-Particles (SeNPs). The results indicated that 4 g/mL SeNPs significantly decreased PDCoV replication on ST cells. SeNPs relieved PDCoV-induced mitochondrial division and antagonized PDCoV-induced apoptosis via decreasing Cyt C release and Caspase 9 and Caspase 3 activation. The above results provide a basis for the development and clinical use of drugs for PDCoV prevention and treatment. The above results provided an idea and experimental basis associated with anti-PDCoV drug development and clinical use.